Grain growth: The key to understand solid-state dewetting of silver thin films. (1st April 2016) - Jacquet, P.; Podor, R.; Ravaux, J.; Teisseire, J.; Gozhyk, I.; Jupille, J.; Lazzari, R.
Abstract: The dynamics of solid-state dewetting of polycrystalline silver thin films in oxygen atmosphere was investigated with in situ and real-time environmental Scanning Electron Microscopy at high temperature combined with Atomic Force Microscopy. Three steps were identified during dewetting: induction, hole propagation without specific rim and sintering. Moreover, it was observed that a very selective grain growth, promoted by surface diffusion, plays a key role all along the process. Graphical abstract: